2018
DOI: 10.1088/1751-8121/aaad47
|View full text |Cite
|
Sign up to set email alerts
|

A two-dimensional lattice equation as an extension of the Heideman–Hogan recurrence

Abstract: We consider a two dimensional extension of the so-called linearizable mappings. In particular, we start from the Heideman-Hogan recurrence, which is known as one of the linearizable Somoslike recurrences, and introduce one of its two dimensional extensions. The two dimensional lattice equation we present is linearizable in both directions, and has the Laurent and the coprimeness properties. Moreover, its reduction produces a generalized family of the Heideman-Hogan recurrence.Higher order examples of two dimen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
22
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(27 citation statements)
references
References 19 publications
5
22
0
Order By: Relevance
“…which is the relation for an SL 3 frieze on each of the sublattices obtained by restricting s + t to have odd/even parity, and can be put in the standard form (18) by a linear change of coordinates. A further application of (19) shows that the corresponding 4 × 4 determinant vanishes for the 2-frieze relation, while in [23] it is shown that there is also a constant 3 × 3 determinant and a vanishing 4 × 4 determinant associated with (14), and in the sequel we prove an analogous result for the new lattice equation (15).…”
Section: Introductionmentioning
confidence: 55%
See 4 more Smart Citations
“…which is the relation for an SL 3 frieze on each of the sublattices obtained by restricting s + t to have odd/even parity, and can be put in the standard form (18) by a linear change of coordinates. A further application of (19) shows that the corresponding 4 × 4 determinant vanishes for the 2-frieze relation, while in [23] it is shown that there is also a constant 3 × 3 determinant and a vanishing 4 × 4 determinant associated with (14), and in the sequel we prove an analogous result for the new lattice equation (15).…”
Section: Introductionmentioning
confidence: 55%
“…corresponding to a wave moving on the lattice with constant velocity −q/p ∈ Q. Similarly, it was noted in [23] that the 5-point lattice equation…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations